2018
DOI: 10.1155/2018/3265918
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein‐I + II Reduces Oxidative Damage and Apoptosis after Traumatic Spinal Cord Injury in Rats

Abstract: After spinal cord injury (SCI), some self-destructive mechanisms start leading to irreversible neurological deficits. It is known that oxidative stress and apoptosis play a major role in increasing damage after SCI. Metallothioneins I and II (MT) are endogenous peptides with known antioxidant, neuroprotective capacities. Taking advantage of those capacities, we administered exogenous MT to rats after SCI in order to evaluate the protective effects of MT on the production of reactive oxygen species (ROS) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…After SCI, spinal cord ischemia is accompanied by subsequent energy exhaustion and ATP deficiency, increasing intracellular calcium concentration and ultimately overproduction of ROS [ 32 ]. Excessive ROS formation increases the oxidative damage of proteins, DNA, and lipids molecules and promotes apoptosis-mediated cell death [ 33 ]. Our results suggested that gavage of maltol significantly promoted the expression of antioxidant-related proteins HO-1 and SOD2 in the SCI mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…After SCI, spinal cord ischemia is accompanied by subsequent energy exhaustion and ATP deficiency, increasing intracellular calcium concentration and ultimately overproduction of ROS [ 32 ]. Excessive ROS formation increases the oxidative damage of proteins, DNA, and lipids molecules and promotes apoptosis-mediated cell death [ 33 ]. Our results suggested that gavage of maltol significantly promoted the expression of antioxidant-related proteins HO-1 and SOD2 in the SCI mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Metallothionein is a protein with special physiological functions and plays a unique role in reducing the toxicity of heavy metals such as cadmium, nickel, and lead, as well as scavenging excessive free radicals, anti-aging, and tumor (Bhandari et al, 2017). Previous studies have shown that metallothionein can provide a stable redox environment and protect cells from oxidative stress by resisting the stress response of various organelles (Rios et al, 2018). Polak et al have shown that mtl-1 and mtl-2 play an important role in ameliorating the cytotoxicity of ZnO NPs (Polak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The local increase in MT expression is related not only to the presence of inflammation but also to decreased apoptosis and increased cell proliferation in, among others, Barrett's esophagus, tongue epithelium, and breast and colorectal cancer [ 83 ]. Rios et al demonstrated in an animal model the antiapoptotic activity of MTs due, for example, to the protective effect on exposure to oxygen free radicals in rats subjected to spinal cord injuries [ 84 ]. By virtue of the likely different immune mechanisms observed in CU and CD and hence the different intensity of apoptosis in intestinal epithelial cells in both diseases, the expression of MTs should also differ between these two groups of patients [ 9 ].…”
Section: Metallothioneins and Their Role In The Regulation Of Inflammationmentioning
confidence: 99%